PENGARUH ELEMEN FRAUD PENTAGON TERHADAP KECENDERUNGAN FRAUD DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERASI - Anggraini, Fadilah Dhiya; Sari, Novita (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study aims to examine the influence of the five elements of Pentagon Fraud (pressure, opportunity, rationalization, ability, and arrogance) on the tendency to commit fraud and the role of religiosity as a moderating variable in State Civil Apparatus (ASN). The study population included ASN who had worked for at least two years in 39 Regional Apparatus Organizations (OPD) in Bengkulu City, with a sample size of 90 respondents selected through purposive sampling. The research instrument was a Likert-scale questionnaire adapted from previous research, with the number of items for each construct adjusted, and its validity and reliability tested. Data were analyzed using multiple linear regression and moderated regression (MRA) with the help of SPSS version 26. The results showed that pressure had a significant positive effect on the tendency to commit fraud, while opportunity had a significant negative effect. Meanwhile, rationalization, ability, and arrogance had no significant effect. Religiosity was shown to weaken the effect of pressure on the tendency to commit fraud, but did not moderate the relationship between other variables. The novelty of this study lies in the integration of religiosity within the Pentagon Fraud framework in the context of regional government ASN, which has practical implications for strengthening integrity values and internal control systems in the public sector.